2022
DOI: 10.3390/cells11233940
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Lonp1 Isoforms in Cancer Cells

Abstract: Lonp1 is a mitochondrial protease that degrades oxidized and damaged proteins, assists protein folding, and contributes to the maintenance of mitochondrial DNA. A higher expression of LonP1 has been associated with higher tumour aggressiveness. Besides the full-length isoform (ISO1), we identified two other isoforms of Lonp1 in humans, resulting from alternative splicing: Isoform-2 (ISO2) lacking aa 42-105 and isoform-3 (ISO3) lacking aa 1-196. An inspection of the public database TSVdb showed that ISO1 was up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, it regulates the Krebs cycle, oxidative phosphorylation, steroid and heme biosynthesis, and glutamine production. LonP1 is upregulated in many cancers, such as lung, breast, colon, prostate, stomach, glioma, pancreatic, endometrial, melanoma cancer and leukemia [ 115 , 116 ]. Gibellini et al demonstrated that LonP1 inhibition increases mitochondrial ROS accumulation, and triggers oxidative stress and apoptosis in cancer cells, while LonP1 overexpression reduces cell death [ 117 ].…”
Section: Molecules Targeting Mitochondrial Homeostasismentioning
confidence: 99%
“…Moreover, it regulates the Krebs cycle, oxidative phosphorylation, steroid and heme biosynthesis, and glutamine production. LonP1 is upregulated in many cancers, such as lung, breast, colon, prostate, stomach, glioma, pancreatic, endometrial, melanoma cancer and leukemia [ 115 , 116 ]. Gibellini et al demonstrated that LonP1 inhibition increases mitochondrial ROS accumulation, and triggers oxidative stress and apoptosis in cancer cells, while LonP1 overexpression reduces cell death [ 117 ].…”
Section: Molecules Targeting Mitochondrial Homeostasismentioning
confidence: 99%
“…Thus, Lonp1 contributes to the solubilization of mitochondrial proteins [ 28 ]. Lonp1 overexpression has been observed in several cancers and has been shown to promote cell proliferation, apoptotic resistance to stresses, and the transformation of tumor cells [ 25 , 29 , 30 ].…”
Section: General Features and Functions Of Lonp1 And Its Implication ...mentioning
confidence: 99%
“…Interestingly, this observation appears to be in opposition to what is seen in other cell types and models, particularly in tumour cells. For example, Lonp1 overexpression in cancer cells, such as colorectal cancer [ 14 , 21 , 30 ], Oral Squamous Cell Carcinoma, and Non-Small Lung Cancer, promotes cell proliferation, apoptotic resistance to stress, and neoplastic transformation [ 29 ]. This apparent contradiction between cancer cells and cardiomyocytes may be due to their different tolerance to ROS levels.…”
Section: The Role Of Lonp1 In Heart Homeostasis and Response To Stressmentioning
confidence: 99%
“…Alternative splicing (AS) allows eukaryotic organisms to produce multiple different transcripts from a limited set of genes, generating diverse protein variants and significantly expanding the proteome’s diversity. AS also diversifies the function of enzymes, which has been identified in numerous organisms (Zanini et al 2022 ; Yung et al 2022 ; Noda et al 2022 ). For instance, Tan et al ( 2023 ) identified an AS variant of the tumor suppressor liver kinase B1 (LKB1), noted as mitochondria-localized LKB1, which exhibited distinct tissue distribution, specific expression patterns, and biological functions compared to the normal splicing product LKB1.…”
Section: Introductionmentioning
confidence: 99%